APA SAJA KOMPONEN COMMOGNITIVE YANG DIKAJI DALAM PEMBELAJARAN MATEMATIKA: SYSTEMATIC LITERATURE REVIEW - Usman, Muhammad Rizal; Farida, Nur; Satriani, Sri; Kristiawati, Kristiawati (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
This study aims to identify and analyze trends in commognitive research in mathematics education, focusing on four main components: word use, mediators, rules, and narratives. Additionally, this study seeks to explore how commognitive theory is applied in mathematics education research and to identify research gaps that can be further developed. The method used in this study is a Systematic Literature Review (SLR), with article searches conducted through the Google Scholar, SINTA, and Scopus databases within the 2015–2025 timeframe. Articles were selected based on strict inclusion and exclusion criteria, resulting in the final analysis of five relevant articles. Each article was classified based on research methods, key findings, and contributions to commognitive theory in mathematics education. The findings indicate that visual mediators and routines are the most frequently studied commognitive components, particularly in the context of technology use and touchscreen interaction in mathematics learning. Additionally, commognitive conflicts were commonly observed in the transition from school to university, particularly in students' understanding of mathematical terminology (word use) and the application of mathematical communication rules (rules). The primary finding of this study reveals that students with higher mathematical understanding tend to construct more argumentative mathematical narratives, while students with lower comprehension tend to rely on mechanical procedures without fully grasping the underlying concepts. For future research, further exploration of word use and narratives is recommended, particularly in the context of elementary and secondary school education.